The alternate form of the above expression is given as follows:
{P(T>=1) = 3/4, P(T = 2) = 3/4 - P(T = 1)}.
Instead of a generic derivative formula, the alternative form can provide you with the numerical equivalent of the derivative at a specific location (where x=a).
Hence, given P(T≥ 1) = P(T = 1) + P(T= 2) = 2/4+1/4;
Se simplify to get:
P(T>=1) = P(T = 1) + P(T = 2) = 3/4
Given that:
P(T>=1) = 3/4; and
P(T = 1) + P(T = 2) = 3/4
Hence,
{P(T>=1) = 3/4, P(T = 2) = 3/4 - P(T = 1)}
Learn more about Alternate Forms at:
https://brainly.com/question/14745567
#SPJ1